2014
DOI: 10.1002/ajp.22354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endoscopic salpingectomy for sterilization of female Formosan macaques (Macaca cyclopis)

Abstract: We evaluated the safety and postsurgical outcomes of endoscopic salpingectomy for sterilization of female Formosan macaques (Macaca cyclopis) as a method of population control. Nineteen adult female Formosan macaques were included in our study. The fallopian tubes of each anesthetized macaque were cauterized and excised endoscopically using a 2.7-mm rigid endoscope system. We recorded the complications encountered, and objectively scored the amount of hemorrhage throughout the procedure. Postoperative ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Previous studies have shown various undesirable side effects associated with castration, ovariectomy or contraceptive agents in primates (41)(42)(43)(44)(45). Conversely, while impeding fecundation, vasectomy and tubectomy keep intact the steroid hormonal functions underpinning normal sexual activity (20,46). Preservation of the gonadal hormones represents the best option when sterilizing wild female macaques as it allows them to keep normal sexual and social behaviors in their group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown various undesirable side effects associated with castration, ovariectomy or contraceptive agents in primates (41)(42)(43)(44)(45). Conversely, while impeding fecundation, vasectomy and tubectomy keep intact the steroid hormonal functions underpinning normal sexual activity (20,46). Preservation of the gonadal hormones represents the best option when sterilizing wild female macaques as it allows them to keep normal sexual and social behaviors in their group.…”
Section: Discussionmentioning
confidence: 99%
“…The technique we describe here is adapted from the endoscopic salpingectomy in wild macaques first demonstrated by P. Martelli in a DVD entitled “Endoscopic Tubectomy in Macaques” for a German company selling endoscopic equipment (Karl Storz-Endoskope) in 2009. Endoscopic salpingectomy has since widely been used for neutering campaigns in Formosan ( 20 ), rhesus ( 14 , 17 ) macaques and quite recently, on a chimpanzee ( Pan troglodytes ) ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Major complications included difficult entry into the abdominal cavity using the Veress needle, intraoperative hemorrhage, and inadvertent cauterization of uterus. Bleeding from the omentum as a result of Veress needle or trocar trauma has also been reported 13 SUMMARY Endoscopy in NHPs is of great value for disease diagnosis, minimally invasive surgery, and research studies. Primate-specific anesthesiology, case management, and surgical anatomy are important prerequisites before performing any endoscopic procedure.…”
Section: Endoscopic Salpingectomymentioning
confidence: 99%